Regulation of USP7: A High Incidence of E3 Complexes. Issue 22 (10th November 2017) - Kim, Robbert Q.; Sixma, Titia K.
Abstract: Ubiquitin (Ub) conjugation is a critical signalling process in eukaryotic cells. The precise regulation of deubiquitination is an important component of this signalling cascade. Here, we discuss how USP7 (or Herpes-Associated Ubiquitin-Specific Protease, HAUSP), one of the most abundant deubiquitinating enzymes, is regulated by complex formation with regulatory proteins and targets. Full activity of USP7 requires that its C-terminal Ub-like domains fold back onto the catalytic domain, to allow the remodelling of the active site to a catalytically competent state by the very C-terminal peptide. This regulatory mode can be modulated by complex formation with other proteins. USP7 is found in a large number of relatively stable complexes with different possible functions. Complex formation can provide recruitment of a target, bring in an E3 Ub ligase, or modulate the activation of the deubiquitinating enzyme activity. These complexes make up potential cellular "switches", using their (de)ubiquitination ability to switch pathways on or off upon cellular signals. Here, we summarize what is known for USP7 complexes, focussing on the prevalence of E3 Ub ligases and how complex formation can affect Ub switches. Graphical Abstract: Highlights: USP7 activity is regulated by itself and interacting proteins. Many of the USP7 interacting proteins are E3 ubiquitin ligases. E3/USP7 complexes can form cellular switches.